Feeling Sick: The Early Years of AIDS in Spain - Allbritton, Dean (Contemporary Hispanic and Lusophone Cultures, 2023)
An Open Access edition of this book is available on the Liverpool University Press website and the OAPEN library as part of the Opening the Future project with COPIM. The earliest traceable accounts of the AIDS outbreak in Spain began to emerge during its political transition to democracy, with small clusters of cases appearing as early as 1981. HIV/AIDS would go on to shape Spain throughout its pivotal period as a fledgling democracy, underpinning the cultural explosions of the Movida, a sharp rise in intravenous drug use, and the struggles of a coalescing LGBT+ community. Feeling Sick: The Early Years of HIV/AIDS in Spain examines the cultural history of these early years of HIV/AIDS in Spain as it has been told through television and print media, ephemeral products of visual culture, fiction film, and the so-called risk groups that lived through the epidemic. The book draws on the work of Raymond Williams to characterize this emergent period within a structure of "feeling sick" and thus defined by discordant voices, disagreement, and meaning-making in a period of history in formation. Through close readings of Spanish visual culture and media alongside analysis of historical and medical documents, it asserts that a structure of feeling sick begins to coalesce around the emergence of HIV/AIDS and traces out a distinctive sense of living through history as it unfolds. By critically evaluating a selection of cultural materials, this book claims that the earliest years of the HIV/AIDS epidemic in Spain reveal common fears about global connectivity, the proliferation of vulnerable ties to others, and the potential of cultural and physical contaminations. Ultimately, Feeling Sick challenges the dominant narratives in which life and disease are seen as separate and unequal, and in which illness is only destructive and devastating. An Open Access edition of this book is available on the Liverpool University Press website and the OAPEN library as part of the Opening the Future project with COPIM.